On the comparability of the production and intermediation approach in banking efficiency studies - Bod'a, Martin; Piklova, Zuzana (Research Papers of Wrocław University of Economics, 2018)
The paper analyses the question of comparability of results that arise from application of the production and intermediation approach in practical efficiency measurement in banking. Its goal is to assess the comparability or congruence of efficiency scores yielded by these two approaches when applied in a case study of Slovak commercial banks for a period of 11 years between 2005 and 2015, using data envelopment analysis (DEA). The paper acknowledges that the chief distinction between the two approaches residing in the treatment of deposits passes into the resulting efficiency scores and troubles their comparability
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 9-25
Keywords: efficiency; commercial banks; production approach; intermediation approach; comparability; efektywność; banki komercyjne; podejście produkcyjne; podejście inermediacyjne; porównywalność